Mutational analysis of NOG in esophageal atresia and tracheoesophageal fistula patients - Murphy, Andrew J. (2011)
PURPOSE: The NOG protein is a secretory antagonist of bone morphogenetic proteins (BMPs). Nog−/− mouse embryos demonstrate proximal esophageal atresia (EA) and distal tracheoesophageal fistula (TEF) compatible with the most common configuration of EA/TEF observed in humans. Four microdeletions that span the NOG locus at 17q22 have been described in human patients having EA/ TEF. We investigated the incidence of point mutations in the coding region of the NOG gene in human EA/TEF. METHODS: DNA was collected from 50 patients previously treated for EA/TEF. PCR was used to amplify the coding region of NOG. To detect single nucleotide polymorphisms (SNPs), amplicons were subjected to temperature gradient capillary electrophoresis (TGCE). Candidate SNPs were directly sequenced. RESULTS: TGCE analysis revealed a SNP in the coding region of NOG in 1 of 50 patients (2%). DNA sequencing revealed a synonymous SNP at position 468 (C–T) of the NOG coding region. CONCLUSION: SNPs in the coding region of the NOG gene are identified infrequently in human cases of EA/TEF. Further investigation of SNPs in the promoter region of NOG is warranted, as is the effect of synonymous SNPs on NOG mRNA stability.